A novel approach for diabetes: recent evidence on endoluminal liners. (May 2013) - Romero-Talamás, Héctor; Brethauer, Stacy A
SUMMARY  The obesity–diabetes pandemic is a devastating contemporary public health issue that for decades has been steadily on the rise. As knowledge and experience have been progressively acquired, numerous strategies and techniques for its management have arisen. Currently, only surgical treatment offers significant and durable results in terms of weight loss, and remission or improvement of comorbidities. With the objective of offering less invasive alternatives, several endoscopic devices have been introduced. Only the endoscopic duodenal–jejunal liner effectively simulates the bypass component of certain bariatric procedures. Initially designed for weight loss, this endoluminal artifact later proved to also provide a powerful metabolic effect. Although it is still in an investigational phase, the device is a promising tool for the treatment of obesity.